Formulation And Evaluation Of Self-Emulsifying Drug Delivery Systems Of Azithromycin To Enhance Its Penetration Through The Epithelial Tight Junctions - Assi, Reem Abou (2018)
Azithromycin (AZM) is a macrolide antibiotic used for the treatment of a number of bacterial infections. It is known to have a low oral bioavailability (37 %) due to its relatively high molecular weight, incomplete solubility and/or poor intestinal permeability, which is potentially restricting its intestinal absorption. To overcome these drawbacks liquid and solid self-emulsifying drug delivery systems (L-SEDDs and S-SEDDs) of AZM were prepared in an attempt to enhance its solubility, and altering its cellular penetration, which might improve its oral bioavailability.